Analysis Of Inpatient Satisfaction Of National Health Insurance Towards The Quality Of Health Services In The Hospital: Literature Review - Sitti Aulia Ramadhani S; Hermiaty Nasruddin; Abbas Zavey Nurdin (Jurnal EduHealth, 2024)
The hospital is functioning as place reference service health For health centers, especially in matter care and recovery patient. focus The main hospital is to organize maintenance healing and rehabilitation patients, and as the result is important for they For own system management efficient operations For give service health to patient. The purpose of study This is For know level satisfaction patient take care BPJS hospitalization against quality service House sick. Research This using the literature review process. Information taken from the Garuda Ristekbrin electronic database and Google Scholar. For look for relevant articles, terms search used is satisfaction BPJS patients at home sick. Search the found 3,856 items. Articles that are not fulfil condition For entered No accepted. For analysis studies Here, a total of 13 publications were selected with score satisfaction patient take care BPJS hospitalization about service House sick. Articles This show How elements quality maintenance health influence satisfaction JKN patients at home pain. Tangible, reliability, responsiveness, assurance, and empathy are elements that influence satisfaction JKN patients at home sick. Hospital must always make an effort increase standard service for satisfaction patient increase.